A study on the effectiveness of promotion for Islamic product at Agrobank Segamat / Norshafiqah Md Dasuki - Md Dasuki, Norshafiqah (2011)
The effectiveness of promotion is the important thing for each of company in order to attract the customers to sustain towards the product and service. The strategy to increase the product will become a heart of the company to get better profitability`s and stronger sustainable competitive advantage. So, the promotions are very important to give information about the product to the customer. The problem in Agrobank Segamat is the managing director of Agrobank, Datuk Ahmad Said has target in year 2015 all of the products in Agrobank will be in Islamic system and no more in conventional system but until year 2010 conventional product is still higher and then Islamic product. Research methodology is the way to obtain information about the characteristic or parameters of a population by using the descriptive research as research design and the population is the customer over 6, 18, 21 and 50 years old who are using the Islamic product at Agrobank Segamat. For sampling design, the researcher uses probability and simple random sampling while the sample size is 100. The researcher uses secondary and primary data for data collection method data. Other than that, the researcher uses survey questionnaire and personal interview to collect the data. SPSS is using in data analysis and work schedule is the timetable for the researcher to complete this thesis. From the analysis, the level of the effectiveness of promotions for Islamic product at Agrobank is effective and the most effective promotional tool for these products is sales promotion. There are relationship between effectiveness of promotion and all five promotional tool with the level of each relationship whether very high relationship, high relationship, moderate relationship and low relationship. Other than that, there are several recommendations to improve the effectiveness of promotional tools for Islamic products in sales promotion, personal selling and public relation.